Resilience of MSMEs in Surakarta City: Integrating digital transformation and local economic resilience based on Javanese cultural values - Rohmad Suryadi; Lusi Oktaviana; Kholid Syaifulloh; Anita Maulani Yusnia; Ratih Ayu Rafiaulia (Priviet Social Sciences Journal, 2026)
Micro, Small, and Medium Enterprises (MSMEs) play a strategic role in sustaining local economies in Indonesia, particularly in culturally embedded cities such as Surakarta. Despite their growing number and contribution to employment, many MSMEs remain vulnerable to economic shocks, technological disruption, and unequal access to digital resources. This study aims to examine the resilience of MSMEs in Surakarta by analyzing the interaction between digital transformation, Javanese cultural values, and the legal–institutional environment that shapes the digital economy. Using a qualitative descriptive approach, this study employs a literature review methodology drawing on peer-reviewed journal articles, government reports, and policy documents related to MSME resilience, digitalization, and local economic development. The findings indicate that Javanese cultural values, including gotong royong, nrimo ing pandum, tepa slira, and ajining dhiri, function as social capital that strengthens social cohesion, psychological endurance, and ethical business practices among MSME actors. Digital transformation contributes positively to business resilience by expanding market access and improving operational efficiency; however, its impact remains uneven due to disparities in digital literacy, human resource capacity, and institutional support. Furthermore, the study highlights the importance of adaptive state regulation and legal certainty in ensuring inclusive digital transformation for MSMEs. This research concludes that MSME resilience in Surakarta emerges from the integration of cultural capital, digital capability, and responsive governance, underscoring the need for context-sensitive and collaborative policy approaches to support sustainable local economic development.